Transcriptional changes detected in fecal RNA of neonatal dairy calves undergoing a mild diarrhea are associated with inflammatory biomarkers - Rosa, Fernanda (PLoS One, 2018)
After birth, a newborn calf has to adapt to an extrauterine life characterized by several physiological changes. In particular, maturation of the gastrointestinal tract in a new environment loaded with potential pathogens, which can predispose neonatal calves to develop diarrhea, and is a major cause of morbidity and mortality during the first 4 wks of life. We aimed to investigate the inflammatory adaptations at a transcriptomic level in the gastrointestinal (GI) tract to a mild diarrhea in neonatal dairy calves using RNA isolated from fresh fecal samples. Eight newborn Jersey male calves were used from birth to 5 wks of age and housed in individual pens. After birth, calves received 1.9 L of colostrum from their respective dams. Calves had ad-libitum access to water and starter grain (22% CP) and were fed twice daily a total of 5.6 L pasteurized whole milk. Starter intake, body weight (BW), fecal score, withers height (WH), and rectal temperature (RT) were recorded throughout the experiment. Blood samples were collected weekly for metabolic and inflammatory profiling from wk 0 to wk 5. Fresh fecal samples were collected weekly and immediately flash frozen until RNA was extracted using a Trizol-based method, and subsequently, an RT-qPCR analysis was performed. Orthogonal contrasts were used to evaluate linear or quadratic effects over time. Starter intake, BW, and WH increased over time. Fecal score was greatest (2.6 ± 0.3) during wk 2. The concentrations of IL-6, ceruloplasmin, and haptoglobin had a positive quadratic effect with maximal concentrations during wk 2, which corresponded to the maximal fecal score observed during the same time. The concentration of serum amyloid A decreased over time. The mRNA expression of the proinflammatory related genes TLR4, TNFA, IL8, and IL1B had a positive quadratic effect of time. A time effect was observed for the cell membrane sodium-dependent glucose transporter SLC5A1, for the major carbohydrate facilitated transporter SLC2A2, and water transport function AQP3, where SLC5A1 and AQP3 had a negative quadratic effect over time. Our data support the use of the fecal RNA as a noninvasive tool to investigate intestinal transcriptomic profiling of dairy calves experiencing diarrhea, which would be advantageous for future research including nutritional effects and health conditions.